Analisa Makna Ruang Pada Baileu Di Pulau Seram Barat, Maluku - Hadisuwarno Tanzil; Lintu Tulistyantoro; Stephanie Melinda Frans (Intra, 2019)
West Seram people has many different culture heritages on many aspects like social, economy, belief, and culture. One form of heritage was manifested in traditional Baileu architecture. This diversity has not only found in the physical form of architecture, but also in the meaning of concept and spatial structure (place) formed on Baileu reviewed from local’s culture. West Seram people have rich in meaning Baileu. Belief in ancestors has an important role to determine the meaning of space in Baileu on West Seram Island. Theory approaches used is field cosmological primordial from Koentjaraningrat and Jakob Sumardjo. The research method and analysis used was triangulation, which check and correct obtained data or information from different varieties and perspectives to reduce as much bias as possible during the data analysis. The analysis result show that the meaning of space is inseperable from human activity. It’s because space was formed from experience of human senses which created perception and thoughts. This was also reflected in Baileu on West Seram Island’s image, where the belief in the spirit of ancestor influence the values and norms of the local people to create cultures.